ON THE IMPORTANCE OF ETHNOPEDAGOGICAL TRADITIONS IN THE UZBEK PEOPLE (Web of Teachers: Inderscience Research, 2024)
The complexity and versatility of Uzbek traditions cover all aspects of public life as a social phenomenon. While national traditions are primarily associated with the social aspects of people's lives and express feelings or characteristics that are united and universal for the entire nation as a whole, national traditions represent family life belonging to the qualities of this people. Unlike traditions within a people, not all customs are the same, and a particular tradition is based on the observance of different customs in different places.